MENINGKATKAN PEMAHAMAN PENDIDIKAN SEKS PESERTA DIDIK MELALUI BIMBINGAN KELOMPOK - Sari, Dwi Meila; Purwanti, Purwanti; Endang, Busri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to improve the understanding of sex education in students through group guidance services in class XI Madrasah Aliayah Negri 1 Pontianak. The method used in this research is descriptive method in the form of collaborative class action research. Data collection techniques used are direct observation techniques, direct communication in the form of interviews and indirect communication in the form of a questionnaire. Data analysis techniques that calculate the value and percentage. Based on the results of data analysis showed that in the first cycle obtained 60% in the category enough. While in cycle II 78% in good category on implementation of group guidance. From the implementation of research cycle I and II showed that group guidance services can improve understanding of sex education of students in class XI MIA 1 Madrasah Aliyah Negeri 1 Pontianak.Â Keywords: Understanding, Sex Education, Group Guidance